2014
DOI: 10.1007/jhep01(2014)136
|View full text |Cite
|
Sign up to set email alerts
|

Holographic entanglement entropy in imbalanced superconductors

Abstract: Abstract:We study the behavior of holographic entanglement entropy (HEE) for imbalanced holographic superconductors. We employ a numerical approach to consider the robust case of fully back-reacted gravity system. The hairy black hole solution is found by using our numerical scheme. Then it is used to compute the HEE for the superconducting case. The cases we study show that in presence of a mismatch between two chemical potentials, below the critical temperature, superconducting phase has a lower HEE in compa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 76 publications
(91 reference statements)
1
4
0
Order By: Relevance
“…Hence we conclude that the non-monotonicity of entanglement as a function of internal (P ) or external magnetic fields (h) may be used as a general signature of superconductivity. This also means that entanglement at the FFLO state of spin-imbalanced systems has a BCS-like behavior, similar to what has been reported in holographic superconductors [22].…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Hence we conclude that the non-monotonicity of entanglement as a function of internal (P ) or external magnetic fields (h) may be used as a general signature of superconductivity. This also means that entanglement at the FFLO state of spin-imbalanced systems has a BCS-like behavior, similar to what has been reported in holographic superconductors [22].…”
Section: Introductionsupporting
confidence: 81%
“…Several FFLO features have been revealed, including spontaneous breaking of spatial symmetry in the pair correlation [16,17], analytical expression for the critical polarization P C below which the FFLO superfluidity takes place [18], regimes of stability [19] and temperature effects [20]. In contrast though, little is known about the relation between FFLO and entanglement, except from a few reports in gravity systems [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the p-wave superconductor has lower entanglement entropy. The behavior of holographic entanglement entropy for imbalanced holographic superconductor was considered in [20]. It was found that entanglement entropy for this imbalanced system decreases with the increase of imbalance in chemical potentials.…”
Section: Introductionmentioning
confidence: 99%
“…For holographic superconductors, we expect to use the HSC as a probe to capture the richer information of phase transition. Thus, it is meaningful to further analyze the behavior of HSC in other holographic superconductors, such as unbalanced holographic superconductors [50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%